The Manual of strategic planning for cultural organizations a guide for museums, performing arts, science centers, public gardens, heritage sites, libraries, archives, and zoos - Lord, Gail Dexter 1946- (Rowman & Littlefield, 2017)
"This revision of the 2007 Manual of Strategic Planning for Museums has been expanded to be relevant to a broader group of cultural organizations"--Provided by publisher.